Methane Conversion Under Mild Conditions Using Semiconductors and Metal-Semiconductors as Heterogeneous Photocatalysts: State of the Art and Challenges - Januario, Eliane Ribeiro; Silvaino, Patrícia Ferreira; Machado, Arthur Pignataro; Moreira Vaz, Jorge; Spinace, Estevam Vitorio (Frontiers in Chemistry, 2021)
The processes currently used in the chemical industry for methane conversion into fuels and chemicals operate under extreme conditions like high temperatures and pressures. In this sense, the search for methane conversion under mild conditions remains a great challenge. This review aims to summarize the use of heterogeneous photocatalysts for methane conversion into valuable products under mild conditions. First, a brief presentation of photochemical conversion of methane is provided and then the focus of this review on the use of heterogeneous as photocatalysts for methane conversion are described. Finally, the main challenges and opportunities are discussed.